Microbial Profile of High Vaginal swab from Women of Reproductive Age Group in a Tertiary Care Hospital – A Cross-sectional Study: - Beena, Beena Jha; Sharma, Manisha; Bhatt, Chandra Prakash; Neupane, Sushmita (Medical Journal of Shree Birendra Hospital, 2025)
Introduction: Vaginal infections can be caused by Staphylococcus aureus, Enterococcus species, beta haemolytic streptococcus, Neisseria species, Escherichia Coli, Klebsiella species and Candida species. If untreated they can lead to pelvic inflammatory disease (PID), which can cause long-term sequelae, such as tubal infertility, ectopic pregnancy, reproductive dysfunction and adverse pregnancy outcomes. Thus, the aim of this study is to identify organism causing vaginal infections among the women of child bearing age. Methods: A prospective cross-sectional study was conducted in the Department of Microbiology at Kathmandu Medical College and Teaching Hospital, Sinamangal. Two vaginal specimens were collected. Direct Gram staining and bacteriological cultures were carried out for all specimens. The antibiotic sensitivity of aerobic bacterial isolates was performed by Kirby Bauer disc diffusion technique as per the CLSI guidelines. Version of the statistical package for the social sciences (SPSS) version 20.0 was used to analyse the data. Results: Out of 80 vaginal swab culture, 11(13.75%) showed pathogenic growth, where as 69(86.25%) showed normal vaginal flora. Escherichia coli was the most prevalent vaginal pathogen i.e. 81.81% followed by K. pneumoniae and P. aruginosa. All the organism isolated were 100% sensitive to Tigecycline, Polymyxin B, Amikacin and Piperacilin/Tazobactam. Conclusions: E. coli was the most prevalent vaginal pathogen i.e. 81.81% followed by K. pneumoniae and P. aruginosa. Maximum number of aerobic vaginitis (AV) were from the age group of 26-30 yrs. In our study pathogenic bacteria were found more frequently than candida. Therefore, practice of empirical antifungal therapy without taking high vaginal swab needs to be revised. The use of appropriate antibiotics along with antifungal drugs may be benificial.